(untitled) (Journal of Contemporary Philology, 2018)
Choosing childhood, city and dream as a threefold Ariadne’s thread uncoiling through the paths of the labyrinth of his work, Urošević chronotopically hybridizes, through a harmonious combination, the real and the imaginary, a dream and reality, the near and the far, experience and memory, Order and Adventure, life and creation. If childhood is a paradise lost, a true emanation of the wondrous, and city, in a sense, the centre of the world, a cosmos preserving the palimpsestic traces of the past, while at the same time being also adjustable to personal yearnings, then dream denotes ‘the end’ of the familiar reality and ‘the beginning’ of some other, fantastic or surreal reality, subject to different laws and logic, but equally true and crucial to our existence.